URGENSI PENGEMBANGAN SARANA DAN PRASARANA BOLA VOLI DALAM MENDUKUNG PEMBELAJARAN PADA PROGRAM STUDI PENDIDIKAN KEPELATIHAN OLAHRAGA UNIVERSITAS MUHAMMADIYAH BONE - Andi Sri Rafiqa Hayu; Nurfadilla; Muh Surya Akbar; Roy Kamaruddin; Sri Suciangriani; Dian Febrianti; Sherli; Safril; Muh Aldi; Arfin Patikawa Purna (STKIP Subang, 2026)
This study aims to examine the urgency of developing volleyball facilities and infrastructure to support the learning process in the Sports Coaching Education Study Program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Bone. This study employed a qualitative approach using a descriptive method. The research informants consisted of the Head of the Study Program, the volleyball course lecturer, students, and the facilities and infrastructure manager. Data were collected through observation, interviews, and documentation. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The credibility of the findings was ensured through source and technique triangulation.The findings indicate that volleyball facilities and infrastructure are essential in supporting the effectiveness of the learning process. The availability of volleyball courts, nets, balls, and supporting training equipment was found to facilitate students' understanding of volleyball techniques and coaching practices. However, the study also identified limitations in the quality and quantity of the existing facilities, indicating the need for further development. The development of volleyball facilities and infrastructure is therefore considered an important priority for improving the quality of learning and supporting the implementation of practical courses within the study program.In conclusion, the development of volleyball facilities and infrastructure is a fundamental requirement for supporting the learning process in the Sports Coaching Education Study Program at Universitas Muhammadiyah Bone. Sustainable support and commitment from both the study program and the university are therefore needed to improve the availability and quality of these facilities, thereby enhancing the quality of educational services and strengthening the implementation of sports coaching education.